Manejo integrado del nematodo (Radopholus similis) en el cultivo de banano (Musa AAA)” - Medina Olea, Roosvelt Alfonso (2020)
Bananas are one of the main crops in Ecuador, generating jobs, as well as foreign exchange for the country. The attack or presence of a pest would cause a decrease in the quality and yield of the crop. Nematodes are one of the main pests of the banana crop, Radopholus similis, causing radical deterioration, which leads to low crop yield, and also low quality. The nematode Radopholus similis attacks the roots of banana cultivation plants, causing losses in production. Among the effects caused by this nematode, is the weakening of the plant and difficulty in absorbing nutrients or water, preventing the plant from doing it normally. Among the control measures that are taken to control this nematode are: the chemical control that must be carried out in cycles, about three applications per year, the biological control based on the Trichoderma spp fungus, which surrounds the nematode in its mycelium by injecting antibiotic metabolites and enzymes, the cultural control that is carried out on the plants that are going to be sown, performing a plant surgery (such as eliminating injured parts) and previous disinfection by immersing them in chemical treatments for 15 minutes.